Urban Governance and Service Delivery Mechanism: A Slum Based Study of Dhaka Metropolitan - Uddin Suman, Shihab; Akter Shanta, Mahbuba (South Asian Journal of Social Sciences and Humanities, 2025)
Urban governance encompasses the mechanisms used to manage cities, including public administration and the delivery of services. Effective urban governance is crucial for achieving sustainable and inclusive growth. This study focuses on the most underprivileged group in society: slum dwellers. It uses a quantitative approach to examine the issue. Dhaka Metropolitan is the primary area of focus, with data obtained from the ‘Urban Informal Settlement Survey-2016.’ The author analyzes the functions of the Dhaka Metropolitan service delivery system and the main responsibilities of each department. Next, the study describes the living conditions and livelihoods of slum residents using descriptive statistics, including pie charts, bar diagrams, and tables. MS Excel is used for this purpose. The findings highlight the limitations of slum administration and the reasons behind unreliable service delivery. Additionally, the provision of basic services is inadequate, leading to poor living conditions for the urban poor. This study shows that governance in the Dhaka Metropolitan slums has several areas for improvement. The service delivery system is not functioning properly. The findings also reveal the quality of life of the urban poor, their heavy dependence on informal non-agricultural sectors, poor housing conditions, and limited access to essential services, including healthcare, potable water, sanitation, and education. Ultimately, integrated policies can help address the challenges of service delivery and governance in urban slums by fostering accountability and transparency.